15‐year follow‐up of the Second Nordic Mantle Cell Lymphoma trial (MCL2): prolonged remissions without survival plateau. (5th July 2016) - Eskelund, Christian W.; Kolstad, Arne; Jerkeman, Mats; Räty, Riikka; Laurell, Anna; Eloranta, Sandra; Smedby, Karin E.; Husby, Simon; Pedersen, Lone B.; Andersen, Niels S.; Eriksson, Mikael; Kimby, Eva; et al.
Summary: In recent decades, the prognosis of Mantle Cell Lymphoma (MCL) has been significantly improved by intensified first‐line regimens containing cytarabine, rituximab and consolidation with high‐dose‐therapy and autologous stem cell transplantation. One such strategy is the Nordic MCL2 regimen, developed by the Nordic Lymphoma Group. We here present the 15‐year updated results of the Nordic MCL2 study after a median follow‐up of 11·4 years: For all patients on an intent‐to‐treat basis, the median overall and progression‐free survival was 12·7 and 8·5 years, respectively. The MCL International Prognostic Index (MIPI), biological MIPI, including Ki67 expression (MIPI‐B) and the MIPI‐B including mIR‐18b expression (MIPI‐B‐miR), in particular, significantly divided patients into distinct risk groups. Despite very long response durations of the low and intermediate risk groups, we observed a continuous pattern of relapse and the survival curves never reached a plateau. In conclusion, despite half of the patients being still alive and 40% in first remission after more than 12 years, we still see an excess disease‐related mortality, even among patients experiencing long remissions. Even though we consider the Nordic regimen as a very good choice of regimen, we recommend inclusion in prospective studies to explore the benefit of novel agents in the frontline treatment of MCL.